The Effect of Murabahah and Musyarakah Financing on Profitability at PT BPRS HIK Parahyangan Period 2018-2022 - Ira Ariyanti; Ganjar Santika; Ikmal Mumtahaen (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The purpose of this study to be achieved, among other things, is to find out that murabahah financing has an effect on profitability at PT BPRS HIK Parahyangan. To analyze musyarakah financing has an effect on profitability at PT. BPRS HIK Parahyangan To analyze murabahah financing and musyarakah financing together, they affect the profitability of PT. BPRS HIK Parahyangan. This study uses a quantitative method, using statistical procedures. This research is descriptive analysis in nature, namely research that seeks to describe the current problem solving based on data. Based on the results of the study it can be concluded (1) murabahah financing has a positive effect on profitability, so it is concluded that the higher the murabahah financing, the higher the profitability income (2) musyarakah financing has significant effect on profitability. (3) murabaha and musyarakah financing have an effect. Based on the results of the F test that the statistical probability value is 0.000111 0.05, so H0 is rejected and H1 is accepted. Thus it can be concluded that there is an influence of the independent variables (murabaha and musyarakah) on profitability.